2009
DOI: 10.1016/j.nucmedbio.2008.11.005
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo analysis of [64Cu-NO2A-8-Aoc-BBN(7–14)NH2]: a site-directed radiopharmaceutical for positron-emission tomography imaging of T-47D human breast cancer tumors

Abstract: Introduction-Human breast cancer, from which the T-47D cell line was derived, is known to overexpress the gastrin-releasing peptide receptor (GRPR) in some cases. Bombesin (BBN), an agonist for the GRPR, has been appended with a radionuclide capable of positron-emission tomography (PET) imaging and therapy. 64 Cu-NO2A-8-Aoc-BBN(7-14)NH 2 (NO2A=1,4,7-triazacyclononane-1,4-diacetate) has produced high-quality microPET images of GRPR-positive breast cancer xenografted tumors in mice.Methods-The imaging probe was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 33 publications
(57 reference statements)
3
39
0
2
Order By: Relevance
“…Clinical studies 2 Journal of Nanomaterials in women using radio-bombesin derivatives have shown successful radionuclide imaging of breast tumors [7][8][9][10]. In particular, the GRPR is highly expressed in T47D human breast cells, and that is the reason why these cells have been used as tumor models to evaluate new bombesin probes [6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies 2 Journal of Nanomaterials in women using radio-bombesin derivatives have shown successful radionuclide imaging of breast tumors [7][8][9][10]. In particular, the GRPR is highly expressed in T47D human breast cells, and that is the reason why these cells have been used as tumor models to evaluate new bombesin probes [6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that occupation of this non-chelating carboxylate of NOTA, as in our bifunctional NO2A, may not alter the native structure of the Cu-NOTA complex. We have recently evaluated 64 Cu-NO2A-8-Aoc-BBN(7-14)NH 2 radiopharmaceutical ( Figure 4) to be used as a PET targeting agent for primary or metastatic breast cancer disease (Prasanphanich et al, 2009). In this study, we were able to prepare high specific activity 64 Cu-NO2A-8-Aoc-BBN(7-14)NH 2 conjugate in very high radiochemical yield and to evaluate the 1) targeting capacity of 64 Cu-NO2A-8-Aoc-BBN(7-14)NH 2 for GRPr-positive tissues in vivo; 2 ) p a r t i c u l a r r o u t e s o f c l e a r a n c e ; a n d 3 ) e x t e n t o f r e t e n t i o n o f radiopharmaceutical in radiosensitive tissues.…”
Section: Micropet Imaging With Copper-64-bbn Conjugatesmentioning
confidence: 99%
“…These data provided the molecular basis for exploiting GRPR as a target for cervical cancer diagnosis. GRPR is already being studied for diagnostic purposes in other types of cancer, like breast and prostate cancer, with promising results [14,15,16,17]. However, to date no studies have evaluated GRPR expression in cancer using immunocytochemistry.…”
Section: Introductionmentioning
confidence: 99%